PTU-071 Cause of Death in the Exeter Inflammatory Bowel Disease (IBD) Population. (4th June 2013) - Wesley, E; Beddoes, B; Forbes, A; Clarke, M; Daneshmend, T K; Ahmad, T
Abstract : Introduction: Recent meta-analyses of population based IBD mortality studies have shown no increase in standardised mortality ratio for ulcerative colitis (UC) 1, but a small increase for Crohn's disease (CD) 2 . 26–50% of deaths in CD patients were related to the underlying IBD diagnosis 2 . The aims of this study were to investigate the death cause distribution in a well defined IBD population and to establish the proportion of deaths related to the underlying diagnosis or treatment. Methods: Retrospective case note review to establish cause of death of all patients on the Exeter IBD database who died in the 9yr period until 31.12.2011. Cases were reviewed by 2 clinicians to establish cause of death and ascertain whether it was related to the underlying diagnosis or treatment. Results: 143 deaths, 82 male. 87 had UC, 46 CD and 10 IBD unclassified. Mean age at diagnosis was 58 (11 – 94). Mean duration of disease at time of death was 17 years (0–61). The median age of death was 72.5 and 79 years for CD and UC respectively ( P = 0.001, 95% CI –13 - –3 years). The underlying disease or treatment was implicated in the cause of death in 35/143 (23%) patients and was more common in CD compared to UC patients (37 vs. 18%, P = 0.03). There was no change over time in the proportion of related deaths. 13/143 (9%) had a diagnosis of colorectal cancer at the time of death; in 8 this was the primary cause of death. 8 had Primary Sclerosing Cholangitis, all of whom died of related complications. 8 patients had a haematological malignancy including 3 patients with colonic lymphomas, 1 with chronic myeloid leukaemia, 2 with non-Hodgkin's lymphoma and 1 with peripheral T cell lymphoma. Half of these patients had previously been prescribed thiopurines. 10 died during emergency admission for acute IBD. 3 had coexisting enteric infection. 2 died from perforations (gastric and ileal). 7 died of post-operative complications of IBD surgery (3 emergency cases, 4 elective). 94/143 (66%) died of conditions unrelated to IBD (including 23 cardiac, 21 respiratory causes). 38 (27%) died of cancer. A cause of death could not be established for 14 patients. Conclusion: CD patients died at a younger age compared with UC patients and were more likely to die from a complication of IBD or treatment. The proportion of IBD related deaths has not changed within the time period of this study. Disclosure of Interest: None Declared References: Jess, T et al. Am J Gastro 102, 609–617 (2007). Duricova, D. et al. IBD 16, 347–353 (2010).